Sheikh Marouf Al-Nodehi System in Situation Science analytical study - البنجويني, أ.م.د. محمد عبدالله احمد (Sulaimani Journal for Humanities, 2024)
Praise be to God who guided us to Islam, and peace and blessings be upon the best of those He sent as a Prophet of peace, and upon his family and companions, the people of piety, faith, and harmony. Every era has its needs and requirements, and each era has those who fulfill and realize a portion of those requirements and needs. Sheikh Muhammad Ma'ruf ibn Mustafa ibn Ahmad al-Nawdahi al-Shahrazuri al-Barzanji al-Shafi'i lived during the twelfth and thirteenth centuries, eras rife with strife and problems, devoid of peace and stability. Al-Nawdahi lived in Iraq during part of the Mamluk period, which resembled the Mamluks of Egypt. He also witnessed the rule of thirteen emirs, a time of great political turmoil. Born in this era, his scholarly and social contributions emerged clearly, as if he were born in this time and place to address the challenges of these two periods. He began teaching and writing at an early age, despite the deteriorating political and social conditions in Iraq, and particularly in the Sulaymaniyah region, during his lifetime. He left behind numerous scholarly works and writings in various fields, including commentaries, abridgments, and versifications. He passed away, may God have mercy on him, in 1254 AH (1838 CE) in the city of Sulaymaniyah and was buried in a well-known cemetery in Sivan. Among his scholarly endeavors was his interest in Islamic sciences, including the science of etymology. He versified the book on etymology known among scholars and students as "Al-Risalah al-'Adudiyyah" (The 'Adudiyyah Treatise), "Al-Risalah al-Wad'iyyah" (The Treatise on Etymology), or "Risalah fi al-Wad'" (A Treatise on Etymology), by 'Adud al-Din al-Iji (d. 756 AH/1355 CE). He was 'Abd al-Rahman ibn Ahmad ibn 'Abd al-Ghaffar, Abu al-Fadl. The Sheikh, may God have mercy on him, versified it in sixty-seven verses, encompassing everything that Sheikh al-Iji, may God have mercy on him, had said. This science serves as a link between linguistics, jurisprudence, philosophy, and logic, and is known in our time as the science of terminology or terminological sciences. The study of linguistic conventions and their impact on linguistic thought, both ancient and modern, falls within the sphere of interest of specialists in Arabic language and literature, and researchers in related fields in general. It is also closely connected to other branches such as poetry, grammar, and other Arabic sciences. Language represents the spiritual essence of national, social, and religious identity. It is the substance of culture and civilization, and the repository of the eternal divine message. Arabic is inseparable from Islam, and Muslim scholars need it to understand their religion and fulfill their religious obligations, drawing from its authentic source. It is the only means of understanding Islamic law. Scholars, both past and present, have considered the study of grammar, morphology, and other related disciplines a prerequisite for being a mujtahid (one qualified to exercise independent legal reasoning), because there are certain meanings that cannot be grasped without them. Thus, the rank of ijtihad (independent legal reasoning) depends upon it.
Keywords: The system; the sheikh; the knowledge; the situation